A city of multiple hearts: historic squares of Budapest from the 19th century to the present. - Szívós, Erika (Deutsches Institut für Urbanistik, 2019)
Budapest is one of those European cities which do have a historic centre but do not possessone dominant main square today. The article traces the evolution of Budapest as amulti-focal city, concentrating on the network of its historic squares and seeking explanationsfor the city's polycentric character. Among the explanations, historical discontinuities will be featured alongside radical inner-city reconstruction projects, carried out at the turn of the 19th and 20th centuries; that was the time when the original town hall and town hall square of the Pest side disappeared, together with much of the Pest inner city's premodern urban tissue. Subsequent sections emphasize further, unrealized plans of grandiose inner-city reconstruction in various phases of the city's history, including the failed attempts of establishing a new central "forum" in the interwar period, the cancelled plans of communist governments to refashion the inner city in the spirit of "socialist" architecture, and the never-completed project of erecting a new, central City Hall throughout the 20th and early 21st century. The article pays special attention to the functional diversity of historic squares, highlighting various types of squares which have augmented each other since the time of their construction and which all carry some functions of single-centre towns' traditional main squares. As far as the present physiology of Budapest is concerned, today's municipal government structure and the extensive autonomy of the individual districts will also be identified among the reasons for the city's multi-focal nature.
Keywords: Großstadt; Hauptstadt; Polyzentralität; Stadtplatz; Historischer Platz; Platzfunktion; Stadtgeschichte